Imperialism and Notions of Indigenous Inadequacy in the Philippines - Hawkins, Michael (Silliman Journal, 2023)
This paper explores how American imperialism has dictated the Philippines' colo-nial legacy through carefully constructed notions of indigenous inadequacy. Arbi-trary standards of "modernity", "nation-state", and "citizenship" allegedly justified the United States' civilizing colonial mission in the Philippines. Though both Ameri-cans and Filipinos spoke fondly of progress and equality, the fluid nature of these standards created social, civic, and economic gaps between the metropole and the colony that could never be actually transcended. The shifting notions of mo-dernity ensured the perpetual "inadequacy" of Filipinos relative to their imperial US overlords. This phenomenon continues today. The term "developing nation" provides a good example. What is it these nations are developing towards? What else, but the continually shifting standards of "citizenship" and "nation-state" that ultimately define modernity? The unfortunate reality is that such nations will never "develop" because they have been forced to internalize notions of inadequacy which are supported and perpetuated by the shifting realities of "modernity". In this sense, US rule has proven to be the most detrimental era of Philippine colonial history.